An analysis about the Angel Investor in Brazil, regulations, risks and benefits (Research, Society and Development, 2022)
The entrepreneurial process in its beginning is often difficult and needs financial support for its realization. Angel investment is an investment modality, created in the United States, which has been developing in Brazil in recent years, with recent regulation in the country. In this way, this article developed a bibliographic research, of  qualitative  nature, on the theme of angel investment in Brazil, reflecting on the risks and benefits of this type of investment and detailing the current legislation in force of this type of corporate investment. It was visualized that the angel investor is an individual who invests in a particular company with growth potential, with a possible return on the part of the company. This type of investment is still unknown by both investors and potential entrepreneurs.